Resilience as a concept for understanding family caregiving of adults with Chronic Obstructive Pulmonary Disease (COPD): an integrative review. Issue 2 (11th October 2016) - Rosa, Francesca; Bagnasco, Annamaria; Aleo, Giuseppe; Kendall, Sally; Sasso, Loredana
Abstract: Aims: This paper was a report of the synthesis of evidence on examining the origins and definitions of the concept of resilience, investigating its application in chronic illness management and exploring its utility as a means of understanding family caregiving of adults with Chronic Obstructive Pulmonary Disease. Background: Resilience is a concept that is becoming relevant to understanding how individuals and families live with illness, especially long‐term conditions. Caregivers of adults with Chronic Obstructive Pulmonary Disease must be able to respond to exacerbations of the condition and may themselves experience cognitive imbalances. Yet, resilience as a way of understanding family caregiving of adults with COPD is little explored. Design: Literature review – integrative review. Data sources: CINAHL, PubMed, Google Scholar and EBSCO were searched between 1989–2015. Review methods: The principles of rapid evidence assessment were followed. Results: We identified 376 relevant papers: 20 papers reported the presence of the concept of resilience in family caregivers of chronic diseases patients but only 12 papers reported the presence of the concept of resilience in caregivers of Chronic Obstructive Pulmonary Disease patients and have been included in the synthesis. The term resilience in Chronic Obstructive Pulmonary Disease caregiving is most often understood using a deficit model of health.